IIED - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The International Institute for Environment and Development (IIED) has been working for the last two decades to promote sustainable development in the Third World. It carries out its role of promoting sound management and sustainable use of natural...